2000
DOI: 10.1210/jcem.85.10.6862
|View full text |Cite
|
Sign up to set email alerts
|

The Desmopressin Test in the Differential Diagnosis between Cushing’s Disease and Pseudo-Cushing States

Abstract: Differentiating Cushing's disease (CD) from pseudo-Cushing (PC) states may still be difficult in current practice. Because desmopressin (1-deamino-8D-arginine vasopressin, DDAVP), a vasopressin analogue, stimulates ACTH release in patients with CD but not in the majority of normal, obese, and depressed subjects, we investigated its ability to discriminate CD from PC states. One hundred seventy-three subjects (76 with active CD, 30 with PC, 36 with simple obesity, and 31 healthy volunteers) were tested with an … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
60
1
2

Year Published

2002
2002
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(66 citation statements)
references
References 27 publications
3
60
1
2
Order By: Relevance
“…A potential limitation of the use of this test is represented by the existence of false negative responses in patients with Cushing's disease; these were found in 10 -20% of patients (27,28,30). Furthermore, we obviously cannot rule out that some of the patients currently classified as in remission will experience a later recurrence, resulting in an underestimation of the positive predictive value of the test and overestimation of its negative predictive value.…”
Section: Discussionmentioning
confidence: 98%
“…A potential limitation of the use of this test is represented by the existence of false negative responses in patients with Cushing's disease; these were found in 10 -20% of patients (27,28,30). Furthermore, we obviously cannot rule out that some of the patients currently classified as in remission will experience a later recurrence, resulting in an underestimation of the positive predictive value of the test and overestimation of its negative predictive value.…”
Section: Discussionmentioning
confidence: 98%
“…Although the method requires confirmation and does suffer from some limitations -in particular, like the DDAVP test (4,22) and, theoretically, the DEX/CRH test (3)(4)(5), it cannot be applied in patients with ACTH-independent CS -we suggest its adoption as a second-level test in subjects with normal/high plasma ACTH, who need a differential diagnosis between CD and PC.…”
Section: Discussionmentioning
confidence: 99%
“…The resulting SE and SP, despite the broad CI, exceeded even those of diagnostic tools such as the DDAVP test and the DEX/CRH test, which are considered as the most appropriate second-line tools to differentiate CD from PC (3)(4)(5)(6)(7)22). Table 3 Human CRH (hCRH) test: diagnostic performance of the parameters (peak and basal ACTH and cortisol), alone and combined, in subjects with and without ACTH-dependent Cushing's syndrome (CS).…”
Section: Discussionmentioning
confidence: 99%
“…Because desmopressin (1-deamino-8D-arginine vasopressin, DDAVP), a vasopressin analogue, stimulates ACTH release in patients with CS but not in the majority of normal, obese, and depressed subjects, it has been used to investigated its ability to discriminate CS from pseudo-Cushing states (54,55). In these studies, a plasma peak ACTH increase equal to or greater than 6 pmol/L (27 pg/mL), indicated by ROC analysis, allowed the best discrimination between patients with CS and the other groups, with a sensitivity of 86.8%, a specificity of 90.7%, and a diagnostic accuracy of 89%.…”
Section: Other Second-line Diagnostic Tests To Screen For Csmentioning
confidence: 99%